(untitled) (EUROPEAN AND ASIAN LAW REVIEW, 2024)
This article attempts to assess the development of the institute of state guarantees in the labor law of the Russian Federation at the present time. The assessment of changes is assumed in the context of external and internal political circumstances. A number of legislative initiatives introduced in the State Duma of the Federal Assembly were analyzed, which are aimed at changing the envisaged scope of state guarantees for some categories of workers and the emergence of new categories of workers enjoying state guarantees. These legislative initiatives are compared with changes in the labor legislation of some states - former republics within the USSR. It is concluded that at present the institution of state guarantees of labor rights is developing haphazardly (chaotically), which negatively affects the preservation of the balance of interests of subjects of labor law. This conclusion is based on the results of the analysis of some legislative initiatives, which showed that when introducing amendments, the legislator sometimes violates the basic rules of legal technique; lays down obviously discriminatory grounds for providing guarantees (on the basis of gender); in order to ensure guarantees, unreasonably increases the volume of employers’ obligations to employees, while distancing the state from financing the implementation of new obligations; uses labor law instruments to compensate for social risks, when the state does not have the right to provide guarantees to employees.